Reputation, Quality, Exclusivity : Peer Review in Vocational Education and Training research - Rödel, Bodo [Verfasser] (Zenodo, 2024)
"Peer review is a recognized, although not uncontroversial, procedure for quality assurance of publications in science. It is particularly important in the scientific publication process. There are studies that deal with peer review itself, but there are no works that aim at peer review in Vocational Education and Training (VET) research. The article first presents the state of research and then presents the results of a survey on the subject of peer review, which was carried out in the area of German-language VET research. The aim of the survey is to obtain an initial assessment of the importance of peer review from scientists working in a discipline of VET research. Three perspectives are considered: readers of publications, authors of s publications and reviewers in peer reviews." (Author's abstract ; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; 370; Berufsbildungsforschung; Publikationsverhalten; Peer Review; Qualitätssicherung; Open Access